Pertimbangan Putusan Hakim Perkara Harta Bersama di Pengadilan Agama Tembilahan - Azmil Fauzi Fariska (Hukum Keluarga Islam IAIN LANGSA, 2021)
This research was motivated by the decision of the Tembilahan Religious Court judges who decided the joint property case in which the judge decided the Plaintiff (husband) got 1/4 while the Defendant (wife) got 3/4 of the shared property. However, Article 97 in the Compilation of Islamic Law states that: